Long-term Visual Outcomes of Intravitreal Bevacizumab in Inflammatory Ocular Neovascularization (2009)
Purpose To assess the long-term role of bevacizumab (Avastin; Genentech Inc, South San Francisco, California, USA) in inflammatory ocular neovascularization. Design Retrospective multicenter consecutive case series of inflammatory ocular neovascularization. Methods settings: Multicenter institutional and private practices. study population: Patients with inflammatory ocular neovascularization in one or both eyes of varying etiologies who failed standard therapy. intervention: Intravitreal injection of bevacizumab. main outcome measures: Improvement of best-corrected visual acuity (BCVA) expressed as logarithm of minimal angle of resolution (logMAR), and decrease in central foveal thickness as measured by optical coherence tomography at 6, 12, 18, and 24 months of follow-up. Results Mean logMAR BCVA (central foveal thickness) following intravitreal bevacizumab was as follows: baseline, 0.65 (6/27 or 20/90) (338 ?m; 99 eyes of 96 patients); 6 months, 0.42 (6/16 or 20/53) (239 ?m; 2.0 injections; 81 eyes); 12 months, 0.39 (6/15 or 20/49) (241 ?m; 2.3 injections; 95 eyes); 18 months, 0.40 (6/15 or 20/50) (261 ?m; 3.0 injections; 46 eyes); and 24 months, 0.34 (6/13 or 20/44) (265 ?m; 3.6 injections; 27 eyes). Paired comparisons revealed significant visual improvement at 6 months of 2.4 lines (P = .000), at 12 months of 2.5 lines (P = .000), at 18 months of 2.5 lines (P = .001), and at 24 months of 2.2 lines (P = .013). Paired comparisons revealed significant central foveal flattening at 6 months of 78 ?m (P = .000), at 12 months of 85 ?m (P = .000), at 18 months of 90 ?m (P = .003), and at 24 months of 77 ?m (P = .022). Three eyes developed submacular fibrosis and 1 eye submacular hemorrhage. Conclusion Intravitreal bevacizumab led in the long-term to significant mean visual improvement of ?2.2 lines and significant foveal flattening in a wide variety of inflammatory ocular diseases without major complications. Choroidal neovascularization (CNV) and neovascularization of the disc or elsewhere (NVD/E) in the retina can be an occasionally late sequela of inflammatory chorioretinal diseases,1 and rarely an early manifestation.2 Our group has previously reported the 3-month results of intravitreal bevacizumab (Avastin; Genentech Inc, South San Francisco, California, USA) in inflammatory ocular neovascularization in 84 eyes. Intravitreal bevacizumab led to short-term significant visual improvement and regression of inflammatory ocular neovascularization in a wide variety of inflammatory ocular diseases.3 The long-term safety profile of bevacizumab, and visual prognosis in inflammatory ocular neovascularization, may be jeopardized by submacular fibrosis,4, 5 cystoid macular edema (CME),6, 7, 8 or spread of chorioretinal atrophy. The objective of this report is to assess the long-term safety and efficacy of intravitreal bevacizumab in a retrospective collaborative case series study of inflammatory ocular neovascularization. Methods Consecutive cases of inflammatory ocular neovascularization resistant to corticosteroid with or without antimicrobial therapy and/or immunosuppression treated with intravitreal bevacizumab and followed for more than 6 months were included in the present analysis. The cases were contributed by members of the American Society of Retina Specialists and the American Uveitis Society as detailed elsewhere.3 Intravitreal bevacizumab was injected using a 30-gauge needle in a sterile manner after topical anesthesia and povidone instillation in the lower cul-de-sac. Bevacizumab aliquots were prepared in the hospital pharmacies of the corresponding institution. A standardized spreadsheet was used to collect the clinical data. Cases with prior CME, diabetes mellitus, or age-related macular degeneration were excluded. Most of the patients had initially been treated in a stepwise fashion with high-doses of oral corticosteroid, with or without intraocular or sub-Tenon corticosteroid or immunosuppressive therapy (as monitored by a rheumatologist). All patients signed an informed consent after detailed information about the limited experience, potential side effects, and the off-label usage of the drug. Best-corrected visual acuity (BCVA) was assessed using either Early Treatment Diabetic Retinopathy Study (ETDRS) or Snellen charts (half-and-half) and listed as logarithm of minimal angle of resolution (logMAR) equivalents. Retreatment was done when there was recurrent activity evaluated by funduscopy, fluorescein angiography (leakage, growth of CNV), or optical coherence tomography examination. Differences between final and initial BCVA or central foveal thickness (CFT) were tested using paired Student t test. For small sample size comparisons, nonparametric tests were used. Further associations were performed using one-way analysis of variance (ANOVA) or ?2 test for continuous and categorical variables, respectively. All analysis was conducted using SPSS 13.0 statistical package (SPSS Inc, Chicago, Illinois, USA), and a P value less than .05 was considered significant. Results Ninety-nine consecutive eyes of 96 patients, 33 male and 63 female (78 White, 9 Asian, 8 Hispanic, and 1 Black) with a mean age of 39 years, were examined at baseline and followed up between 6 months and 24 months (TABLE 1, TABLE 2). The right eye was involved in 55 subjects and the left in 44 subjects (3 patients having bilateral disease). Uveitis was active in 26 eyes at the time of ocular neovascularization. Forty-one patients (44 eyes) were taking oral, periocular, or intraocular corticosteroids or other immunosuppressive agents. Thirty-three eyes received 0.1 ml (2.5 mg) of intravitreal bevacizumab and 66 eyes received 0.05 ml (1.25 mg). The diagnosis was punctate inner choroidopathy (23), multifocal choroiditis with panuveitis (19), ocular histoplasmosis (13), idiopathic (12), serpiginous choroiditis (9), Vogt-Koyanagi-Harada disease (6), ocular toxoplasmosis (5), Eales disease (4), sarcoidosis (2), sympathetic ophthalmia (2), tuberculosis (2), acute placoid pigment epitheliopathy (1), and birdshot choroiditis (1).